Homelessness : exploring the new terrain - Kennett, Patricia, 1959-; Marsh, Alex (Policy, 1999)
Analysis that links the phenomenon of homelessness to wider debates about the changing social and economic environment remains relatively underdeveloped. This important book brings together contemporary theoretical debates and original empirical research in order to explore the nature, experience and impact of social change in the context of emerging risks and uncertainties.